Amphiphobic nanoparticle, preparation method and application

By using the interface reaction in the preparation of double -sparse nanoparticles to form a double -sparse nanoparticle, the problem of low -fluoride compound reaction efficiency in the existing technologies has been solved, and efficient fluoride reactions and nanopartal preparation have been achieved. Wetness and heat roll recovery rate.

CN119371945AActive Publication Date: 2025-01-28CHINA PETROLEUM & CHEMICAL CORP +3

Patent Information

Application Number
CN202310919459.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-25
Publication Date
2025-01-28
Estimated Expiration
2043-07-25

AI Technical Summary

Technical Problem

The preparation method of the double-salt agent in the prior art does not consider the dissolution and distribution of fluorine-containing compounds in solution and the reaction and binding efficiency with matrix silica particles, polymer particles, carbon nanotubes, etc., and usually requires a temperature increase reaction. .

Method used

By adding the nanoprocal front drive and amino -containing compounds to the water phase solution, the fluoride -containing compound is added to the oil phase solution, and the oxidation of the interface reaction and the Michael bonus reaction to form double sparse nanoparticles. change.

Benefits of technology

Achieve the efficient enrichment of fluorine -containing components on the surface of double -sparse nanoparticles, improve the response utilization rate, and the response can be carried out at room temperature, which improves the moisture and linear expansion rate of the water and oil on the surface of the rock heart. Rolling recovery rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371945A_ABST
    Figure CN119371945A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of drilling fluid, in particular to an amphiphobic nanoparticle, a preparation method and application. The invention provides a preparation method of amphiphobic nanoparticles. The preparation method comprises the following steps: S1, adding a nanoparticle precursor and an amino-containing compound into a solvent I to obtain a water-phase solution; s2, adding a fluorine-containing compound into a solvent II to obtain an oil phase solution; s3, mixing the water-phase solution with the oil-phase solution to obtain a mixed solution I, adding an oxidizing agent and an accelerant into the mixed solution I, stirring, washing and drying to obtain the amphiphobic nanoparticles. According to the preparation method, particle surface fluorination is achieved through interface reaction, more fluorine-containing components can be enriched on the particle surfaces, the utilization rate of fluorine-containing compounds is high, and the reaction can be conducted at normal temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of drilling fluid, and in particular to an ambisphobic nanoparticle, a preparation method and an application thereof. Background Art

[0002] Tight oil and gas reservoirs have high shale content and are prone to hydration expansion and dispersion, resulting in pore throat blockage. At the same time, the lithology of the core is poorly cemented, and the cementation between rock particles is loose and easy to break. In addition, tight oil and gas reservoirs are prone to water lock damage, and reservoir damage is diverse. Single, commonly used reservoir protection technology has limited protection effects on the reservoir.

[0003] Adding hydrophobic and oleophobic double repellents to the drilling fluid can significantly reduce the surface energy of the wellbore, and change the wettability of the rock surface from hydrophilic and oleophilic to hydrophobic and oleophobic, thereby reducing the entry of foreign liquid into the reservoir, while inhibiting the hydration, dispersion and expansion of the wellbore rock, and improving the stability of the wellbore. The double repellent reservoir protection technology system can maintain the stability of the wellbore through "plugging", "reducing filtration loss" and "hydrophobic and oleophobic", which can effectively release liquid lock, reduce or avoid the damage caused by liquid to the reservoir, and improve the development efficiency of tight oil and gas reservoirs.

[0004] At present, the amphiphilic agents added to water-based or oil-based drilling fluids to maintain the stability of the well wall mainly include amphiphilic silica micro-nano particles, styrene and methacrylate polymer nanoparticles, and carbon nanotubes (CNTs). The methods for preparing amphiphilic agents mainly include: reaction with fluorine-containing compounds in solution or emulsion. For example, patent application CN114149796A (an amphiphilic fluorine-containing nanofluid and its preparation method and application) discloses a fluorine-containing nanofluid that can convert the wettability of hydrophilic and lipophilic reservoirs into amphiphilic properties. The amphiphilic nanofluid has silica particles as the core and fluorine-containing polymers as the shell. The core silica particles are modified with a double-bond coupling agent and then polymerized with fluorine-containing monomers at 80°C to form an amphiphilic shell. Patent application CN111499792B (amphiphobic nanometer plugging agent for oil-based drilling fluid and its preparation method and application) provides an amphiphobic nanometer plugging agent for oil-based drilling fluid and its preparation method, which mainly utilizes long-chain alkyl esters such as styrene and isooctyl acrylate and organic fluorine monomers such as hexafluorobutyl acrylate and dodecafluoroheptyl methacrylate to obtain amphiphobic nanoparticles by step-by-step emulsion polymerization at 75-85°C. Patent applications CN114350332A (bionic and amphiphobic high-efficiency water-based drilling fluid) and CN113698796B (super amphiphobic agent for high-temperature resistant water-based drilling fluid) disclose a carbon nanotube amphiphobic agent, which is first modified by a silane coupling agent containing a double bond and then obtained by reacting with a perfluorosulfonyl halide in a solution at 50-100°C.

[0005] In the prior art preparation method of the amphiphilic agent, the dissolution and distribution of the fluorine-containing compound in the solution and the reaction and binding efficiency with the matrix silica particles, polymer particles and carbon nanotubes are not considered, and the reaction usually requires an elevated temperature. Summary of the invention

[0006] In order to solve the above problems in the prior art, the present invention proposes an ambisphobic nanoparticle, a preparation method and an application thereof.

[0007] In a first aspect, the present invention provides a method for preparing amphoteric nanoparticles, comprising the following steps:

[0008] Step S1: adding a nanoparticle precursor and an amino compound into a solvent I to obtain an aqueous solution;

[0009] Step S2: adding a fluorine-containing compound into solvent II to obtain an oil phase solution;

[0010] Step S3: The aqueous phase solution and the oil phase solution are mixed to obtain a mixed solution I, an oxidant and a promoter are added to the mixed solution I, and the mixture is stirred, washed, and dried to obtain the amphiphilic nanoparticles.

[0011] As a specific embodiment of the present invention, the volume ratio of the oil phase solution to the water phase solution is 3:1 to 1:3.

[0012] As a specific embodiment of the present invention, solvent II is one or more of n-hexane, cyclohexane and heptane.

[0013] As a specific embodiment of the present invention, the fluorine-containing compound is one or more of perfluorooctylethoxysilane, tridecafluoroheptyl oxirane, and nonafluoropentyl oxirane.

[0014] As a specific embodiment of the present invention, the concentration of the fluorine-containing compound in the oil phase solution is 0.01 to 0.06 mol / L.

[0015] As a specific embodiment of the present invention, the amino compound is one of triethylenetetramine, tetraethylenepentamine and aminopropyltriethoxysilane; and the concentration of the amino compound in the aqueous solution is 0.02-0.12 mol / L.

[0016] As a specific embodiment of the present invention, the stirring rate is 5000-8000 rpm.

[0017] As a specific embodiment of the present invention, the oxidant includes sodium periodate or ammonium persulfate; the concentration of the oxidant in the aqueous solution is 0.003-0.006 g / mL. The concentration of the oxidant in the aqueous solution is calculated as the ratio of the mass of the oxidant to the volume of the solvent I.

[0018] As a specific embodiment of the present invention, the promoter is triethylamine or 1,8-diazabicyclo[5.4.0]undec-7-ene, and the concentration of the promoter in the aqueous solution is 0.1-0.3 mg / mL. The concentration of the promoter in the aqueous solution is calculated as the ratio of the mass of the promoter to the volume of the solvent I.

[0019] As a specific embodiment of the present invention, the nanoparticle precursor is a polyphenol compound; the solvent I is an acid-base buffer solution I;

[0020] The polyphenolic compounds are tannic acid or catechol;

[0021] Preferably, the concentration of the polyphenol compound in the aqueous solution is 0.02 to 0.08 mol / L;

[0022] Preferably, the acid-base buffer solution is a Tris-HCl buffer solution, and the pH value of the acid-base buffer solution is 6.5 to 8.5.

[0023] As a specific embodiment of the present invention, the nanoparticle precursor is silicon dioxide nanoparticles, the solvent I includes an acid-base buffer solution II and ethanol, and the volume ratio of the acid-base buffer solution to ethanol in the solvent I is 1:1-3;

[0024] The silica nanoparticles are amino-containing silica nanoparticles or epoxy-containing silica nanoparticles;

[0025] Preferably, the concentration of the silica nanoparticles in the aqueous solution is 0.2 to 0.5 g / mL;

[0026] Preferably, the acid-base buffer solution II is a Tris-HCl buffer solution, and the pH value of the acid-base buffer solution II is 6.5 to 8.5.

[0027] The second invention provides an amphiphobic nanoparticle, wherein the nanoparticle is a fluorinated polyphenol nanoparticle, and is prepared by the preparation method provided by the first aspect of the invention.

[0028] The polyphenol compound is oxidized in an aqueous solution under the pH environment specified by the present invention and the action of an oxidant to form a quinone structure, and then reacts with an amino compound through Michael addition or Schiff base reaction. At the same time, the reactants are stacked, self-polymerized and deposited through π-π interactions to form nanoparticles.

[0029] At the same time, at the water-oil interface, the fluorinated silane coupling agent hydrolyzes and reacts with the -NH- functional groups on the surface of the interfacial polyphenol nanoparticles, thereby loading the nanoparticle surface with fluorinated groups and obtaining surface amphiphobic properties. Figure 2 shown.

[0030] Preferably, the particle size of the fluorinated polyphenol nanoparticles is 50 to 210 nm.

[0031] In a third aspect, the present invention provides an amphiphilic nanoparticle, which is a fluorine-containing silica nanoparticle prepared by the preparation method provided by the first aspect of the present invention.

[0032] Silica nanoparticles with amino or epoxy functional groups on their surface undergo hydrolysis and condensation reactions with amino compounds and fluorine-containing compounds at the water-oil interface, thereby loading fluorine-containing functional groups on the particle surface and obtaining surface amphiphobic properties. Figure 3 shown.

[0033] Preferably, the particle size of the fluorine-containing silica nanoparticles is 20 to 50 nm.

[0034] In a fourth aspect, the present invention provides a use of the ambisophobic nanoparticles provided in the second aspect of the present invention or the third aspect of the present invention in a drilling fluid.

[0035] In a fifth aspect, the present invention provides a drilling fluid, comprising a base slurry and the amphiphobic nanoparticles provided in the second aspect of the present invention or the third aspect of the present invention, wherein the amphiphobic nanoparticles account for 3wt% of the base slurry content; at 120°C and a pressure difference of 3.5MPa, the filtration loss of the drilling fluid is reduced by 30% to 45% compared with the filtration loss of the base slurry.

[0036] Compared with the prior art, the present invention has the following beneficial effects.

[0037] The preparation method of the amphiphilic nanoparticles provided by the present invention realizes fluorination of the particle surface by interfacial reaction, the fluorine-containing components can be more enriched on the particle surface, the utilization rate of the fluorine-containing compounds is high, and the reaction can be carried out at room temperature. The amphiphilic nanoparticles can improve the water-oil wettability of the core surface, the linear expansion rate of bentonite, and the shale hot rolling recovery rate. The core was immersed in an aqueous dispersion containing 3wt% of amphiphobic nanoparticles for 2 to 4 hours and then taken out. The water contact angle on the core surface was tested to be 150 to 162°, and the oil contact angle was 130 to 150°. 3wt% of the amphiphobic particle aqueous dispersion was added to a bentonite column, and the relative linear expansion rate of the bentonite for 24 hours was tested to be 9% to 15%. The 3wt% amphiphobic particle aqueous dispersion was added to the cuttings, and the shale hot rolling recovery rate was tested to be 81% to 96%. The prepared amphiphobic nanoparticles can be used in drilling fluid to achieve the following performance: 3wt% of the amphiphobic nanoparticles were added to the drilling fluid base slurry, and at 120°C and a pressure difference of 3.5MPa, the base slurry after adding the amphiphobic nanoparticles was tested to reduce the filtration loss of the base slurry by 30% to 45% compared with the base slurry.

[0038] The test method used in the present invention is as follows:

[0039] Wettability test method: ultrasonically disperse the amphiphobic nanoparticles in water to prepare a 3wt% dispersion of the amphiphobic nanoparticles, immerse the core in the 3wt% dispersion of the amphiphobic nanoparticles for 2 hours, take out and dry; use a microsyringe to drop 10μl of water droplets or hexadecane oil droplets on the surface of the dried core piece, use a contact angle meter to test the surface contact angles of the water droplets and oil droplets, measure the contact angles at 5 locations, and calculate the average value to evaluate the wettability of the core surface.

[0040] Bentonite expansion test method: Take 10g bentonite, dry at 105℃ for 24h, press at 4MPa for 5min to get a test bentonite column, press two bentonite columns for each test, and measure their initial height; place the bentonite column on a linear expansion instrument (NP-03 model), add 3wt% of the amphiphobic particle aqueous dispersion, measure the expansion height of the bentonite column for 24h, and measure the relative linear expansion rate:

[0041]

[0042] Among them, h0 is the initial sample height, and h1 is the sample height after immersion for 24 hours.

[0043] The test method for the hot rolling recovery rate of cuttings is as follows: 20g of cuttings with a particle size of 6-10 mesh (1.7-3.35mm) are added to a 3wt% aqueous dispersion of double-repellent nanoparticles, aged at 100℃ for 16h, washed with clean water, sieved through a sieve with a pore size of 0.45mm, dried at 105℃ for 4h, weighed, and the recovery rate of cuttings was calculated.

[0044]

[0045] Among them, m0 is the mass of rock cuttings before hot rolling, and m1 is the mass of rock cuttings recovered after hot rolling.

[0046] Rheological property testing method of drilling fluid: prepare drilling fluid base slurry, the composition of the base slurry is as follows: disperse 20g bentonite in 500mL water, hydrate for 24 hours to obtain soil slurry, add 0.3% caustic soda, 0.2% sulfonate copolymer (DSP-2), 0.2% polyanionic cellulose (LV-PAC), 2% sulfonated phenolic resin (SMP-2), 3% anti-slump loss agent (KFT) and 3% sulfonated asphalt powder (FT-1) in turn to the soil slurry to obtain drilling fluid base slurry, add 3wt% of double-repellent nanoparticles to the base slurry, use a six-speed rotation viscometer to measure the viscosity of the drilling fluid, and calculate the rheological parameters of the drilling fluid.

[0047] Apparent viscosity:

[0048] Plastic viscosity: PV = θ 600 -θ 300 , mPa.s

[0049] Dynamic shear force:

[0050] Where θ 600 ,θ 300 These are the readings of a six-speed viscometer at 600r / min and 300r / min respectively.

[0051] High temperature and high pressure fluid loss determination method:

[0052] The high temperature and high pressure filter loss instrument GGS-71B was used for determination in accordance with the national standard GB / T16783.1-2014.

[0053] High temperature and high pressure filtration loss: FL HTHP =2×FL GGS , mL, pressure difference is 3.5MPa, temperature is 120℃. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 Schematic diagram of preparing amphiphobic micro-nanoparticles by interfacial fluorination reaction of polyphenol or silica particles;

[0055] Figure 2 Schematic diagram of the mechanism of preparing amphiphobic micro-nanoparticles by interfacial fluorination reaction of polyphenols;

[0056] Figure 3 Schematic diagram of the mechanism for preparing amphiphobic micro-nanoparticles by interfacial fluorination reaction of silica particles. DETAILED DESCRIPTION

[0057] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.

[0058] Example 1

[0059] Dissolving tannic acid and aminopropyltriethoxysilane in a Tris-HCl buffer solution (pH=6.5) to obtain an aqueous solution, wherein the concentration of tannic acid in the aqueous solution is 0.02 mol / L, and the concentration of aminopropyltriethoxysilane in the aqueous solution is 0.02 mol / L;

[0060] Dissolving tridecafluoroheptyl oxirane in cyclohexane to obtain an oil phase solution, wherein the concentration of tridecafluoroheptyl oxirane in the oil phase solution is 0.01 mol / L;

[0061] The aqueous solution and the oily solution are mixed to obtain a mixed solution, the volume ratio of the oily solution to the aqueous solution is 3:1, stirring is started, the speed is 8000rpm, sodium periodate and triethylamine are added to the mixed solution, stirred at room temperature for 2h, filtered, washed, and dried to obtain fluorinated polyphenol nanoparticles. The concentration of sodium periodate in the aqueous solution is 0.003g / mL, and the concentration of triethylamine in the aqueous solution is 0.1mg / mL. SEM observation and analysis show that the particle size of the obtained fluorinated polyphenol nanoparticles is 50-70nm.

[0062] Example 2

[0063] Dissolving tannic acid and aminopropyltriethoxysilane in a Tris-HCl buffer solution (pH=7.5) to obtain an aqueous solution, wherein the concentration of tannic acid in the aqueous solution is 0.04 mol / L, and the concentration of tetraethylenepentamine in the aqueous solution is 0.06 mol / L;

[0064] Dissolving nonafluoropentyl ethylene oxide in heptane to obtain an oil phase solution, wherein the concentration of nonafluoropentyl ethylene oxide in the oil phase solution is 0.02 mol / L;

[0065] The aqueous solution and the oily solution were mixed to obtain a mixed solution, the volume ratio of the oily solution to the aqueous solution was 1:3, stirring was started, the speed was 8000 rpm, sodium periodate and triethylamine were added to the mixed solution, stirred at room temperature for 2 hours, filtered, washed, and dried to obtain fluorinated polyphenol nanoparticles. The concentration of sodium periodate in the aqueous solution was 0.004 g / mL, and the concentration of triethylamine in the aqueous solution was 0.2 mg / mL. SEM observation and analysis showed that the particle size of the obtained polyphenol nanoparticles was 120 to 150 nm.

[0066] Example 3

[0067] Dissolve catechol and triethylenetetramine in a Tris-HCl buffer solution (pH=8.5) to obtain an aqueous solution, wherein the concentration of catechol in the aqueous solution is 0.08 mol / L, and the concentration of triethylenetetramine in the aqueous solution is 0.12 mol / L;

[0068] Dissolving perfluorooctylethoxysilane in n-hexane to obtain an oil phase solution, wherein the concentration of perfluorooctylethoxysilane in the oil phase solution is 0.04 mol / L;

[0069] The aqueous solution and the oily solution were mixed to obtain a mixed solution, the volume ratio of the oily solution to the aqueous solution was 1:1, stirring was started, the speed was 5000 rpm, ammonium persulfate and 1,8-diazabicyclo[5.4.0]undec-7-ene were added to the mixed solution, stirred at room temperature for 2 hours, filtered, washed, and dried to obtain fluorinated polyphenol nanoparticles. The concentration of ammonium persulfate in the aqueous solution was 0.006 g / mL, and the concentration of 1,8-diazabicyclo[5.4.0]undec-7-ene in the aqueous solution was 0.3 mg / mL. SEM observation and analysis showed that the particle size of the obtained polyphenol nanoparticles was 180 to 210 nm.

[0070] Example 4

[0071] Dissolving catechol and tetraethylenepentamine in a Tris-HCl buffer solution (pH=8.5) to obtain an aqueous solution, wherein the concentration of catechol in the aqueous solution is 0.06 mol / L, and the concentration of tetraethylenepentamine in the aqueous solution is 0.06 mol / L;

[0072] Dissolving perfluorooctylethoxysilane in cyclohexane to obtain an oil phase solution, wherein the concentration of perfluorooctylethoxysilane in the oil phase solution is 0.03 mol / L;

[0073] The aqueous solution and the oily solution were mixed to obtain a mixed solution, the volume ratio of the oily solution to the aqueous solution was 1:2, stirring was started, the speed was 8000 rpm, sodium periodate and 1,8-diazabicyclo[5.4.0]undec-7-ene were added to the mixed solution, stirred at room temperature for 2 hours, filtered, washed, and dried to obtain fluorinated polyphenol nanoparticles. The concentration of sodium periodate in the aqueous solution was 0.005 g / mL, and the concentration of triethylamine in the aqueous solution was 0.2 mg / mL. SEM observation and analysis showed that the particle size of the obtained fluorinated polyphenol nanoparticles was 90 to 130 nm.

[0074] Example 5

[0075] Dispersing silicon dioxide nanoparticles containing epoxy groups in a mixed solution, wherein the volume ratio of Tris-HCl buffer solution (pH=8.5) to ethanol is 1:1, and then adding aminopropyltriethoxysilane to the mixed solution to obtain an aqueous solution, wherein the concentration of the silicon dioxide nanoparticles in the aqueous solution is 0.2 g / mL, and the concentration of the aminopropyltriethoxysilane in the aqueous solution is 0.04 mol / L;

[0076] Dissolving perfluorooctylethoxysilane in cyclohexane to obtain an oil phase solution, wherein the concentration of perfluorooctylethoxysilane in the oil phase solution is 0.06 mol / L;

[0077] The aqueous solution and the oily solution were mixed to obtain a mixed solution, wherein the volume ratio of the oily solution to the aqueous solution was 3:1, stirring was started at a speed of 8000 rpm, sodium periodate solution and triethylamine were added to the mixed solution, the mixture was stirred for 2 h, filtered, washed, and dried to obtain fluorinated silica nanoparticles; the concentration of sodium periodate in the aqueous solution was 0.004 g / mL, and the concentration of triethylamine in the aqueous solution was 0.2 mg / mL triethylamine.

[0078] SEM observation and analysis showed that the particle size of the obtained fluorine-containing silica nanoparticles was 20 to 30 nm.

[0079] Example 6

[0080] Dispersing the amino-containing silica nanoparticles in a mixed solution, wherein the volume ratio of Tris-HCl buffer solution (pH=8.5) to ethanol is 1:1, and then adding aminopropyltriethoxysilane to the mixed solution to obtain an aqueous phase solution, wherein the concentration of the silica nanoparticles in the aqueous phase solution is 0.5 g / mL, and the concentration of the aminopropyltriethoxysilane in the aqueous phase solution is 0.12 mol / L;

[0081] Dissolving perfluorooctylethoxysilane in cyclohexane to obtain an oil phase solution, wherein the concentration of perfluorooctylethoxysilane in the oil phase solution is 0.04 mol / L;

[0082] The aqueous solution and the oily solution were mixed to obtain a mixed solution, wherein the volume ratio of the oily solution to the aqueous solution was 3:1, stirring was started at a speed of 8000 rpm, sodium periodate solution and triethylamine were added to the mixed solution, the mixture was stirred for 2 h, filtered, washed, and dried to obtain fluorinated silica nanoparticles; the concentration of sodium periodate in the aqueous solution was 0.005 g / mL, and the concentration of triethylamine in the aqueous solution was 0.3 mg / mL.

[0083] SEM observation and analysis showed that the particle size of the obtained fluorine-containing silica nanoparticles was 30 to 50 nm.

[0084] According to the wettability test method, the water and oil-hexadecane contact angles on the core surface were measured, and the results are shown in Table 1;

[0085] According to the bentonite expansion test method, the relative linear expansion rate of the bentonite sample was measured for 24 hours, and the results are shown in Table 1;

[0086] According to the cuttings hot rolling recovery rate test method, the cuttings recovery rate after hot rolling aging was determined. The results are shown in Table 1.

[0087] Table 1 Liquid contact angle, bentonite swelling rate and shale recovery rate on the core surface

[0088]

[0089] From Table 1 we can see that:

[0090] After the surface of the core piece is covered with the prepared amphiphobic nanoparticle dispersion, its surface wettability changes from hydrophilic and oleophilic to super hydrophobic and oleophobic, thus realizing the transformation of surface wettability.

[0091] After adding the prepared amphiphilic nanoparticle dispersion into the bentonite sample, the 24h linear expansion rate of the bentonite sample was significantly reduced compared with the bentonite sample without adding the amphiphilic nanoparticle dispersion.

[0092] The rock chips were added into the prepared amphiphilic nanoparticle dispersion, and after aging, the hot rolling recovery rate of the rock chips was significantly improved compared with the rock chips not added into the amphiphilic nanoparticle dispersion.

[0093] The test results show that the amphiphilicity of the obtained particles can effectively inhibit the adsorption and penetration of water on the shale surface, effectively inhibit hydration expansion, and play an effective role in protecting the shale.

[0094] The drilling fluid base slurry was added with amphiphilic nanoparticles, the content of which was 3wt% of the base slurry. The rheological properties and fluid loss reduction were measured, and the results are shown in Table 2.

[0095] Table 2 Effect of the rheology and filtration properties of the double-repellent nanoparticle drilling fluid prepared in the embodiment

[0096]

[0097]

[0098] From Table 2, we can see that: at room temperature, after adding the obtained amphiphobic nanoparticles, the apparent viscosity of the drilling fluid does not change significantly, the plastic viscosity is slightly reduced, and the dynamic shear force is increased, indicating that the drilling fluid with the addition of amphiphobic nanoparticles has good rheological properties; at the same time, the high temperature and high pressure filtration loss is significantly reduced, and the filtration loss is reduced by 30% to 45%, indicating that the amphiphobic nanoparticles can participate in the formation of mud cakes, making the mud cakes denser.

[0099] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A method for preparing amphoteric nanoparticles, characterized in that: The steps include: Step S1: adding a nanoparticle precursor and an amino compound into a solvent I to obtain an aqueous solution; Step S2: adding a fluorine-containing compound into solvent II to obtain an oil phase solution; Step S3: The aqueous phase solution and the oil phase solution are mixed to obtain a mixed solution I, an oxidant and a promoter are added to the mixed solution I, and the mixture is stirred, washed, and dried to obtain the amphiphilic nanoparticles.

2. The method for preparing double-repellent nanoparticles according to claim 1, characterized in that: The volume ratio of the oil phase solution to the water phase solution is 3:1 to 1:

3.

3. The method for preparing the double-repellent nanoparticles according to claim 2, characterized in that: The solvent II is one or more of n-hexane, cyclohexane, and heptane; and / or the fluorine-containing compound is one or more of perfluorooctylethoxysilane, tridecafluoroheptyl oxirane, and nonafluoropentyl oxirane, and the concentration of the fluorine-containing compound in the oil phase solution is 0.01 to 0.06 mol / L.

4. The method for preparing the double-repellent nanoparticles according to claim 3, characterized in that: The amino compound is one of triethylenetetramine, tetraethylenepentamine and aminopropyltriethoxysilane; the concentration of the amino compound in the aqueous phase solution is 0.02-0.12 mol / L.

5. The method for preparing the double-repellent nanoparticles according to claim 4, characterized in that: The stirring speed is 5000-8000 rpm.

6. The method for preparing the double-repellent nanoparticles according to claim 5, characterized in that: The oxidant includes sodium periodate or ammonium persulfate; the concentration of the oxidant in the aqueous solution is 0.003-0.006 g / mL.

7. The method for preparing the double-repellent nanoparticles according to claim 6, characterized in that: The promoter is triethylamine or 1,8-diazabicyclo[5.4.0]undec-7-ene, and the concentration of the promoter in the aqueous phase solution is 0.1-0.3 mg / mL.

8. The method for preparing the double-repellent nanoparticles according to any one of claims 1 to 7, characterized in that: The nanoparticle precursor is a polyphenol compound; the solvent I is an acid-base buffer solution I; The polyphenol compound is tannic acid or catechol; Preferably, the concentration of the polyphenol compound in the aqueous solution is 0.02 to 0.08 mol / L; Preferably, the acid-base buffer solution is a Tris-HCl buffer solution, and the pH value of the acid-base buffer solution is 6.5 to 8.

5.

9. The method for preparing the amphiphilic nanoparticles according to any one of claims 1 to 7, characterized in that: The nanoparticle precursor is silicon dioxide nanoparticles, the solvent I comprises an acid-base buffer solution II and ethanol, and the volume ratio of the acid-base buffer solution to the ethanol in the solvent I is 1:1-3; The silicon dioxide nanoparticles are silicon dioxide nanoparticles containing amino groups or silicon dioxide nanoparticles containing epoxy groups; Preferably, the concentration of the silicon dioxide nanoparticles in the aqueous solution is 0.2 to 0.5 g / mL; Preferably, the acid-base buffer solution II is a Tris-HCl buffer solution, and the pH value of the acid-base buffer solution II is 6.5-8.

5.

10. A dual-repellent nanoparticle, characterized in that: The amphiphobic nanoparticles are fluorinated polyphenol nanoparticles, which are prepared by the preparation method of amphiphobic nanoparticles according to claim 8; preferably, the particle size of the fluorinated polyphenol nanoparticles is 50 to 210 nm.

11. A dual-repellent nanoparticle, characterized in that: The amphiphobic nanoparticles are fluorine-containing silica nanoparticles, which are prepared by the preparation method of amphiphobic nanoparticles according to claim 9; preferably, the particle size of the fluorine-containing silica nanoparticles is 20 to 50 nm.

12. Use of the amphiphobic nanoparticles according to claim 10 or 11 in drilling fluid.

13. A drilling fluid, characterized in that: The invention comprises a base slurry and the ambiphobic nanoparticles according to claim 10 or 11, wherein the ambiphobic nanoparticles account for 3wt% of the base slurry content; at 120°C and a pressure difference of 3.5MPa, the filtration loss of the drilling fluid is reduced by 30% to 45% compared with the filtration loss of the base slurry.

Citation Information

Patent Citations

  • Bisphosphophore nanoscale plugging agent for oil-based drilling fluids, its preparation method and application

    CN111499792B

  • Super hydrophobic agent for high-temperature water-based drilling fluid

    CN113698796B

  • Amphiphobic fluorine-containing nanofluid as well as preparation method and application thereof

    CN114149796A

  • Bionic and amphiphobic high-efficiency water-based drilling fluid

    CN114350332A

  • Preparation method of super-amphiphobic antifouling transparent coating

    CN113754308A

Cited By

  • Compact rock submicron emulsion type interface modifier as well as preparation method and application thereof

    CN121227323A